Improvement of the lubrication performance of rbd palm stearin as an alternative lubricant under different sliding speeds - Farhanah Azman, Nurul (Strojniški vestnik, 2017)
Vegetable oils have gained global attention to be used as an alternative lubricant to reduce the dependency on natural resources of petroleum- based lubricants due to concern over environmental problems. In this study, a refined, bleached and deodorized (RBD) palm stearin was chosen as the base lubricant, and its lubrication performance was investigated using a pin-on-disk tribotester. A zinc dialkyl-dithiophosphate (ZDDP) additive in concentrations of 1 wt%, 3 wt% and 5 wt% was blended with RBD palm stearin to improve the lubrication performance of the base lubricant. Commercial semi-synthetic oil (SAE15W50) was used for comparison purposes. The experiments were conducted under various sliding speeds (1.5 ms -1 , 2.5 ms -1 and 3.5 ms -1 ) under normal force of 9.81 N for an hour. The lubrication performance of the tested lubricants was presented by the coefficient of friction, wear scar diameter, wear rate, surface roughness and wear worn surface of the pin specimen. The results show that an increase in ZDDP concentrations has improved the lubrication performance of the RBD palm stearin. RBD palm stearin with 5 wt% ZDDP additive shows a smaller coefficient of friction than that of SAE15W50, but creates a slightly larger wear scar diameter and wear rate.
Keywords: koeficient trenja; površinska hrapavost; RBD palmov stearin; stopnja obrabe; tribometer v izvedbi konice na disku